Mothers' Perception and Healthcare Seeking Behavior of Pneumonia Children in Rural Bangladesh - Ferdous, Farzana (Hindawi Publishing Corporation, 2014)
We describe mothers' perception about signs and symptoms, causes of the illness, and healthcare seeking behaviors related to pneumonia and express the major modifiable barriers to seeking timely treatment when their under-5 children had pneumonia in rural Bangladesh. Using focus group discussion, we understood mothers' perception and healthcare seeking behavior of childhood pneumonia. Although mothers described pneumonia as a serious life threatening disease in young children but most of the mothers (n = 24) could not diagnose whether their child had pneumonia or not. Environmental factors such as dust particles, spread from coughing mother, and drinking cold water or playing with water were perceived as the causes for pneumonia. Three common barriers noted were as follows: illness was not perceived as serious enough or distance from healthcare facility or lack of money at household for seeking treatment outside. Most of the rural mothers did not have knowledge about severity of childhood pneumonia.